Clinical isolates of Mycobacterium tuberculosis with different genotypes exhibit distinct host macrophage responses in vitro. Issue 11 (28th November 2022) - Liang, Chen; Li, Xiaomeng; Li, Qiao; Zhang, Xuxia; Ren, Weicong; Yao, Cong; Pang, Yu; Liu, Yi; Li, Chuanyou; Tang, Shenjie
Abstract : Introduction . Mycobacterium tuberculosis ( M.tb ), the causative agent of tuberculosis, can survive as an intracellular parasite after entering macrophages via phagocytosis. M.tb strains are genotypically distinct and engage in diverse pathogen–host interactions, with different host immune responses triggered by different M.tb strains. Importantly, differences in intracellular accumulation and triggering of host macrophage responses during early infection stages are key determinants that shape the final outcomes of host innate immune responses to different M.tb strains. Hypothesis/Gap Statement . Clinical M.tb strains with different genotypes elicit different host innate immune responses in vitro . Aim . This work aimed to compare host innate immune responses elicited by genotypically diverse, clinically derived M.tb strains in vitro . Methodology . RAW264.7 cells were infected with three lineage 2 and lineage 4 clinically derived M.tb strains and strain H37Rv. Strains were evaluated for differences in intracellular growth, induction of macrophage apoptosis, and induction of expression of proinflammatory cytokines and associated pattern recognition receptors. Results . Highly variable cytokine profiles were observed subsequent to RAW264.7 cell infection with the different strains. The Beijing genotype strain, a modern Beijing strain belonging to lineage 2, induced milder host proinflammatory responses and less apoptosis and exhibited greater intracellular growth as compared to the other strains. Moreover, mRNA expression levels of iNOS in Beijing and MANU2 genotype strains exceeded corresponding levels obtained for the T1 genotype strain. Meanwhile, mRNA expression levels of toll-like receptor (TLR)-encoding genes TLR2 and TLR7 in macrophages infected with the Beijing genotype strain were higher than corresponding levels observed in MANU2 genotype strain-infected macrophages. Conclusion . The higher intracellular survival rate and lower level of host cell apoptosis associated with macrophage infection with the Beijing genotype strain indicated greater virulence of this strain relative to that of the other strains. Furthermore, in vitro immune responses induced by the Beijing genotype strain were unique in that this strain induced a weaker inflammatory response than was induced by T1 or MANU2 genotype strains. Nevertheless, additional evidence is needed to confirm that Beijing genotype strains possess greater virulence than strains with other genotypes.